School Violence towards Girls ? a Case of French Muslims - Kopciewicz, Lucyna (INSTED: Interdisciplinary Studies in Education & Society, 2012)
The aim of the article is an attempt of an insight into the culture of a French school and factors that shape it. In this background, a narrower issue of an oppressive effect of school norms that concern pupils? appearance is discussed. The case of French Muslim girls is an interesting departure point for the critical analysis of oppressive actions of Polish teachers. The article presents the background of social tensions caused by ?the Islamic shawl? and the question of changing the media image of French Muslims. The crucial conclusion of the presented analyses are different social competences (resistance against power), which are formed in subjects that undergo oppressive school norms in Poland and France.